Teachers' strategies in teaching speaking skill to junior high school students - Faisal Razi; Asnawi Muslem; Dohra Fitrisia (Universitas Syiah Kuala, 2021)
Improving the speaking skill of the students requires creativity in strategies. Therefore, this research aims to describe the kind of strategies as well as the obstacles. This research used observation sheet and interview guide as the instruments. The subjects of this research were two English teachers who teach the junior high school students at SMP Inshafuddin Banda Aceh. The data were collected by observing and interviewing the teachers. Then, the procedure of data analysis for this research involved data condensation, data display and drawing the conclusion. The result of the first research question of this research described that there are five strategies used by the teachers in teaching speaking skills, namely role play, drilling, games, picture describing, and storytelling. Meanwhile, the result of the second research question described the obstacles faced by the teachers related in applying the strategies. It is suggested for the teachers to be creative in applying several strategies to improve students’ speaking skill. In conclusion, in order to be succeed in applying the strategies, the teachers need to find the solution in overcoming the obstacles while applying the strategies.